Diversity, systematics, and evolution of Cynodonteae inflorescences (Chloridoideae – Poaceae). Issue 3 (3rd April 2018) - Pilatti, Vanesa; Muchut, SebastiÁn E.; Uberti-Manassero, Nora G.; Vegetti, Abelardo C.; Reinheimer, Renata
Abstract : The species of the Cynodonteae tribe show great morphological diversity in their reproductive structures. Previous studies where inflorescences were comparatively analysed in the context of phylogeny have shown that although grass inflorescences seem to be excessively variable, there are certain aspects of inflorescences that store relevant information on the evolution and systematics in Poaceae. We have analysed and compared the inflorescence structures of species belonging to the Hilariinae, Monanthochloinae, Scleropogoninae, and Muhlenbergiinae subtribes. Considering the most relevant morphological characters, the most recurrent types of inflorescences in the lineage were determined by means of a principal coordinates analysis. To understand the evolution of inflorescence morphology, ancestral reconstructions of inflorescence characters were performed using the Bayesian inference method. The results obtained demonstrate that the processes of homogenization and truncation might account for the diversity observed in adult inflorescences. Five different types of inflorescences were identified out of 36 theoretical possibilities. Amongst these, inflorescence type 1 (panicle of spikelets, with a terminal spikelet, non-homogenized, and bearing third- or higher-order branches) was found to be the most frequent in the studied group. Ancestral reconstructions of morphological characters allowed us to suggest that the ancestor of the group might have had an inflorescence with the form of a raceme of spikelets, non-truncated and bearing first-order branches. More complex inflorescences bearing no terminal spikelets and having branches of higher order might have diverged this lineage.